Moral Education of Khamayati in The Preparation of Students of The Military Faculty for Military Service - Ubaydullaev Saidakbar Saydalievich (European Science Publishing, 2023)
This article will present young people in the process of Military education today works, activities and the main ones in their upbringing are carried out in the spirit of patriotism opinions have been expressed on the full range of tasks.
Keywords: Youth, in spirit, upbringing, Military.